If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(4 + -1x) = 4(x + 5) (4 * 8 + -1x * 8) = 4(x + 5) (32 + -8x) = 4(x + 5) Reorder the terms: 32 + -8x = 4(5 + x) 32 + -8x = (5 * 4 + x * 4) 32 + -8x = (20 + 4x) Solving 32 + -8x = 20 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 32 + -8x + -4x = 20 + 4x + -4x Combine like terms: -8x + -4x = -12x 32 + -12x = 20 + 4x + -4x Combine like terms: 4x + -4x = 0 32 + -12x = 20 + 0 32 + -12x = 20 Add '-32' to each side of the equation. 32 + -32 + -12x = 20 + -32 Combine like terms: 32 + -32 = 0 0 + -12x = 20 + -32 -12x = 20 + -32 Combine like terms: 20 + -32 = -12 -12x = -12 Divide each side by '-12'. x = 1 Simplifying x = 1
| 3x-6.2=14.2 | | -8d=-9d+7 | | 30=-5/2u | | 90=(x+2)(y+1.5) | | 7f/3=5 | | m^2-10m+19=-8 | | 5X+3-X=15+X | | 4c=(a-b)/3 | | 49v^2+16=-56v | | b/3=15.2 | | 10n=7n+9 | | log(132-4x)=2 | | 54=d | | 2x+54=24 | | Cos(5x)=0.8 | | 1200m=600 | | -10+c=-4c | | -(8y-3)-(-7y-8)=9 | | 6n=43 | | 1-2n=-10+5-n+4n | | -5+2a-8a=42 | | 3y+21=6y | | 2+3x=5(x-3) | | -3p(p+2)=-30 | | 7e^5x=924 | | -2n+2=-3n-5 | | 11x-3x+90=11x+36 | | a-5+2a-8a=42 | | 8h=168 | | x/10-4=4 | | 7a-11=38 | | 8(-4a-1)=3(10a) |